O setor pesqueiro em portugal - relato de caso - de Arruda, Lia Ferraz; Martins, Priscila Eloi; da Silva, Adriana Figueiredo; de Moraes, Julieta E. Rodini [UNESP]; Vaz-Pires, Paulo; de Almeida Ozório, Rodrigo Otávio; Oetterer, Marília (My University, 2011)
Interviews were conducted with scientific researchers and process industries, bibliographic research and observational technical visits to collect information about the portuguese fishery sector. The relevance of this sector derives essentially from the fact that fish is a key component of food and responsible for large number of jobs within the Portuguese population. With the reduction in catches due to the decline in world's fish stocks the government has encouraged actions of ecological nature to promote the sector sustainability. Actually, the decline in the market expression facilitates the entry of stranger companies from others countries. Entrepreneurs must increase the productivity and provide quality assured products in order to achieve the export market.
The fishery sector in portugal - report study
Keywords: Production; Seafood consumption; Sustainability